Rural-Urban Differentials in Utilization of Artificial Intelligence for Improved Agricultural Production among Crop Farmers in Southeast Nigeria - Emmanuel Ejiofor Omeje; Ikenna Charles Ukwuaba; Kelvin Nnaemeke Nwangwu; Ibrahim Isaac Umaru; Justina Chituru Ibe; Chukwuma Otum Ume; Johnpaul Tochukwu Offorma (Journal of Agricultural Extension)
This study analysed rural-urban differentials in the utilisation of Artificial Intelligence (AI) for improved crop production among farmers in Nigeria. It specifically examined the level of awareness and utilisation of AI, the effect of AI usage on crop production, and the challenges associated with the awareness and utilisation of AI. 316 respondents were selected through multistage sampling, and data were analysed using descriptive statistics and OLS regression. Urban farmers (16.46%) were more aware than rural farmers (10.13%), and the awareness was more among young farmers (17.40%). Most respondents (16.4%) learned about AI through social media. Only 17.09% of farmers used AI, with 11% of those users coming from urban areas. Age (B =-18.57), AI usage (B=3451.890), education (B=86.65), and extension services (B=160.38) were determinants of improved crop production among urban farmers. In comparison, AI usage (B=3499.69), education (B=57.63) and farm size (B=118.56) were the drivers in the rural areas. Rural farmers (m=2.68) were faced with more challenges than urban farmers (m=2.41). Urban farmers face AI disparity (m=2.87) and knowledge gaps (m=3.66), while rural farmers lack access to AI-enabled devices (m=3.47). To improve crop productivity, Nigeria's AI strategy should prioritise awareness campaigns, especially in rural areas.